Asymmetric synthesis of vinylogous β-amino acids and their incorporation into mixed backbone oligomers. Issue 15 (27th March 2017) - Wu, Hao; An, Hongchan; Mo, Shuting (Cynthia); Kodadek, Thomas
Abstract : Vinylogous β-amino acids are constructed using a concise, enantioselective route and shown to be superior building blocks for the construction of chiral oligomers. Abstract : Chiral vinylogous β-amino acids (VBAA) were synthesized using enantioselective Mannich reactions of aldehydes with in situ generated N -carbamoyl imines followed by a Horner–Wadsworth–Emmons reaction. The efficiency with which these units could be incorporated into oligomers with different moieties on the C- and N-terminal sides was established, as was the feasibility of sequencing oligomers containing VBAAs by tandem mass spectrometry. The data show that VBAAs will be useful building blocks for the construction of combinatorial libraries of peptidomimetic compounds.